Never too old for something new: feasibility and long-term outcomes of leadless pacemaker implant in the elderly. (19th May 2022) - Barletta, V; Parollo, M; Mazzocchetti, L; Sbragi, S; Murazzi, E; Canu, A; Giannotti Santoro, M; Della Volpe, S; Zucchelli, G; Bongiorni, MG
Abstract: Funding Acknowledgements: Type of funding sources: None. Elderly patients may be at great risk of complications and present a higher incidence of comorbidities which make challenging PM implant procedure. The use of leadless pacing systems has imposed itself to overcome peri- and post-procedural complications related to the presence of transvenous leads and the post-operative recovery, being a favorable option in elderly patients. The study aimed to investigate feasibility and long-term outcomes of M-TPS implant in a specific patient population, like the elderly, which represent a challenge for conventional cardiac pacing. Methods: Between May 2014 and November 2021, 155 patients (120 males, mean age 78±9 y) underwent M-TPS implantation in our Center, targeting a non-apical site of delivery when feasible. A subgroup of 69 patients (52 males, 75.36%) were older than 80 years. All patients fulfilled standard criteria for PM implantation with specific indication to receive VVI pacing. Study population was divided into two groups according to age (group 1 < 79 years vs group 2≥80 years). The outcome evaluation included electrical performance (capture threshold, pacing impedance, R wave amplitude) before hospital discharge and then followed at 1, 6, and 12 months and then annually. Major complications were defined as life-threatening events, required surgical intervention or any event causing significant hemodynamic instability or resulting in death. Results: In 69/155 cases (52 males, 75.36%) M-TPS was implanted in patients older than 80 years. There were no statistically significant differences between groups for demographics characteristics, except for age. The implant procedure was successful in all cases and no device-related events were registered during follow-up. In particular, no device infection and/or malfunction were reported. Patients were followed-up for an average of 24 months (median 18 months). No differences were observed between groups in procedure duration, single device delivery (group 1 vs group 2: 62.79% vs 65.22%, p=0.75), fluoroscopy time (group 1 vs group 2: 11.46 ±6.12 vs 11.37 ± 8.37 minutes, p=0.23), electrical performance at implant (group 1 vs group 2: pacing threshold 0.56 ± 0.37 V/0.24 ms vs 0.58 ± 0.31 V/0.24 ms, p=0.55; impedance 737.86 ± 173.50 Ohm vs 759.56 ± 255.35 Ohm, p=0.87; R wave amplitude 10.5 ± 5.18 mV vs 9.19 ± 4.45 mV, p=0.14) and at 18 [VB2] month F-U (group 1 vs group 2: pacing threshold 0.64 ± 0.55 V/0.24 ms vs 0.51 ± 0.1 V/0.24 ms, p=0.85; impedance 535.34 ± 102.53 Ohm vs 577.34 ± 69 Ohm, p=0.40; R wave amplitude 12.56 ± 4.56 mV vs 12.00 ± 5.8 mV, p=0.77[VB3] ). Conclusions: The demand for cardiac pacing is strongly related to ageing, driving the clinical practice to look for the best solution for a considered fragile patient population. MTP-S implant is an effective and safe procedure in elderly patients, with similar electrical performance and outcome compared with younger patients at long-term follow.